1986
DOI: 10.1039/c39860000636
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic CO species adsorbed on the surface of scandium, yttrium, and lanthanum oxides

Abstract: The interaction of CO molecules with the surface of Sc, Y, and La oxides leads to the formation of paramagnetic polyatomic surface compounds containing two equivalent carbon atoms and lattice cations; a structure for the adsorbed (CO)2.radical anions which explains their high thermal stability and reactivity has been suggested.The nature of intermediate surface compounds is important in elucidating the mechanism of catalytic reactions involving CO. A large number of variations of the forms of adsorbed CO have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The reactions observed 120 can be described as follows: Some ethylenedione anions are stabilized at the surface, where they are observed by EPR, while others react with electrons to give the diamagnetic C 2 O 2 2ion, which, in turn, undergoes a series of condensation reactions, producing cyclic and linear oxycarbon dianions (C n O n 2-) which have been observed by vibrational spectroscopy. 123,124 Polymeric radical species derived from CO, and similar to those described here for MgO, have been reported on scandium, yttrium, and lanthanum oxides 125 and on zirconium dioxide. 126…”
Section: Radicals Generated From Carbon Monoxidesupporting
confidence: 75%
“…The reactions observed 120 can be described as follows: Some ethylenedione anions are stabilized at the surface, where they are observed by EPR, while others react with electrons to give the diamagnetic C 2 O 2 2ion, which, in turn, undergoes a series of condensation reactions, producing cyclic and linear oxycarbon dianions (C n O n 2-) which have been observed by vibrational spectroscopy. 123,124 Polymeric radical species derived from CO, and similar to those described here for MgO, have been reported on scandium, yttrium, and lanthanum oxides 125 and on zirconium dioxide. 126…”
Section: Radicals Generated From Carbon Monoxidesupporting
confidence: 75%
“…7 They have reported that CO chemisorbed reactively on a Sm 2 O 3 surface to form several types of species, which were also detected on other rare earth oxides. 8 On the other hand, under UHV conditions, no CO chemisorption was observed on rare earth oxide films 2 or single crystal surfaces of a rare earth oxide 3 at room temperature. The characteristic weak adsorption state of CO observed here on the SmO x surface was not stable at room temperature under UHV condition.…”
mentioning
confidence: 98%